Evaluation of antifungal activity of ethanolic extract of 'andrographis echioides' – An Invitro study - K.PUNNAGAI,; D.DARLING CHELLATHAI,; V.P.KARTHIK,; I.GLORY JOSEPHINE, (International Journal of Pharma and Bio Sciences, 2016)
Andrographis echioides is a medicinal plant included in Indian Materia Medica as a remedy for fevers, skin infections. This study was conducted to find out the antifungal activity of the ethanolic extract of the whole plant “Andrographis echioides” using standard agar disc diffusion method. Pulverized whole plant of A.echioides was subjected to soxhlet extraction using organic solvent of ethanol. The antifungal activity of A.echioides extract was done using standard agar disc diffusion method using Sabouraud Dextrose agar (SDA) medium against five strains of fungi. Amphotericin B was the standard positive control and the negative control was DMSO. 20µl of plant extract in varying concentrations were tested & activity was determined by diameter of the zone of inhibition. The ethanolic whole plant extract of A.echioides showed antifungal activity against fungal species candida albicans, Aspergillus flavus, Penicillium spp., Aspergillus niger, Trichophyton in 1000µg concentration of the sample showing the zone of inhibition of 6,7,7,8,5 mm respectively. The ethanolic extract of Andrographis echioides has shown to have significant antifungal activity against Aspergillus niger, Penicillium and Aspergillus flavus species of fungi.